The effects of acupuncture on clinical efficacy and steady-state visual evoked potentials in insomnia patients with emotional disorders: A randomized single-blind sham-controlled trial - Zhang, Leixiao; Deng, Yanli; Hui, Ruting; Tang, Yu; Yu, Siyi; Li, Ying; Hu, Youping; Li, Ning (Frontiers in Neurology, 2023)
The aim of this study was to observe the clinical effects and brain electrical potential changes following acupuncture in the treatment of insomnia patients with mood disorders. Ninety patients with insomnia who met the inclusion criteria were randomly divided into the active acupuncture group (AA group, n = 44) and sham acupuncture group (SA group, n = 46) at a ratio of 1:1. The primary outcome was the total score of the Pittsburgh Sleep Quality Index (PSQI), and the secondary outcomes were the total effective rate, Self-Rating Anxiety Scale (SAS), Self-Rating Depression Scale (SDS) scores, and values of steady-state visual evoked potentials (SSVEP). The two groups received acupuncture or sham acupuncture 10 times (2 weeks). Finally, the total PSQI scores of the AA group and SA group were significantly different (p < 0.05) at 2 weeks (6.11 ± 2.33 vs. 10.37 ± 4.73), 6 weeks (6.27 ± 1.39 vs. 11.93 ± 3.07), 18 weeks (6.32 ± 2.84 vs. 11.78 ± 2.95) and 42 weeks (8.05 ± 3.14 vs. 12.54 ± 2.81). Further analysis found that AA group patients received acupuncture treatment at any age after the same effect (p > 0.05). The SAS and SDS scores of the AA group were also significantly different from those of the SA group at each assessment time point (p < 0.05). The total effective rate of the AA group was 81.82%, while that of the SA group was 30.43% (p < 0.05). There was no significant difference between the AA group and SA group only in the brain potential of the parietal lobe (F4), left temporal lobe (C3) and right temporal lobe (T8) (P > 0.05), but there was a significant difference between other brain regions (P < 0.05). In addition, correlation analysis showed that there was a certain positive correlation between the total PSQI score, SAS score, efficacy level, and SSVEP value in the AA group as follows: C4 and the total PSQI score (r = 0.595, P = 0.041), F3 and SAS score (r = 0.604, P = 0.037), FPz and efficiency level of the frontal lobe (r = 0.581, P = 0.048), and O2 and efficiency level of the occipital lobe (r = 0.704, P = 0.011). Therefore, acupuncture have a good clinical effect on patients with insomnia and emotional disorders and have a significant regulatory effect on abnormally excited brain potentials.